2016
DOI: 10.1212/wnl.0000000000003360
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the phenotype of BICD2 mutations toward skeletal muscle involvement

Abstract: Our findings extend the phenotypic spectrum of BICD2-associated disorders by features of a chronic myopathy and show a pathomechanism of BICD2 defects in skeletal muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 29 publications
3
31
0
1
Order By: Relevance
“…RAB6A staining with confocal microscopy in patient muscle cells revealed a much larger and plane‐wide RAB6A/Golgi‐ER interface. Localization studies indicate that mutant BICD2 aggregates into clusters dotted along the perinuclear region . The authors of this study suggested that the higher Golgi fragmentation correlates with a more severe clinical course, as patients with p.(T703M) variants had the added phenotype of congenital contractures .…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…RAB6A staining with confocal microscopy in patient muscle cells revealed a much larger and plane‐wide RAB6A/Golgi‐ER interface. Localization studies indicate that mutant BICD2 aggregates into clusters dotted along the perinuclear region . The authors of this study suggested that the higher Golgi fragmentation correlates with a more severe clinical course, as patients with p.(T703M) variants had the added phenotype of congenital contractures .…”
Section: Discussionmentioning
confidence: 72%
“…Coimmunoprecipitation experiments indicate that this variant also increases BICD2–dynein interaction, seemingly a gain‐of‐function effect. However, localization studies revealed that whereas wild‐type BICD2 localizes to the Golgi apparatus, vesicles, and microtubular filaments in the perinuclear region, mutated BICD2 accumulates in dense clusters near (or even inside) the nucleus . These aggregates appear to cluster at the microtubule organization center (MTOC), to which dynein‐mediated transport is directed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some patients with MRD13 show clinical evidence of peripheral neuropathy [57]. More recently, BICD2 variant syndrome includes arthrogryposis multiplex congenital with bilateral perisylvian polymicrogyria and a phenotype with chronic myopathy [58, 59]. …”
Section: Sma Plus Syndromesmentioning
confidence: 99%
“…It was first suggested that most affected individuals show a similar, recognizable phenotype . However, in recent years, additional phenotypes have been reported for BICD2 mutations, including juvenile amyotrophic lateral sclerosis (ALS), chronic myopathy, and SMA with cerebellar hypoplasia . Further, de‐novo mutations were reported as causative for severe congenital arthrogryposis, and asymptomatic carriers have been described, suggesting that the phenotypic spectrum may vary substantially …”
mentioning
confidence: 99%